A bioinformatics approach to introduce novel multi-epitope vaccines against Acinetobacter baumannii retrieved from immunogenic extracellular loops of outer membrane proteins. (2022) - Meskini, Maryam; Noori Goodarzi, Narjes; Fereshteh, Sepideh; Bolourchi, Negin; Mirzaie, Amir; Badmasti, Farzad
Abstract: Increasing antibiotic resistance of Acinetobacter baumannii highlights the urgent need to develop an effective vaccine to combat it. Despite all efforts, no approved vaccine against this bacterium is on the market, and attempts are underway to find effective vaccines. Due to their surface exposure, outer membrane proteins (OMPs) are excellent vaccine targets. The extracellular loops of OMPs are highly immunogenic. Therefore, in the present study, we aimed to detect the conserved, exposed, and immunogenic linear B-cell epitopes among sixty-five OMPs available in 35 A. baumannii genomes deposited in the Vaxign database. According to defined criteria (allergenicity, antigenicity, and non-similarity to host), four linear B-cell epitopes were selected as highly immunogenic peptides. Epitope shuffling was performed to select the best arrangements of these epitopes. We proposed six different multi-epitope vaccines consisting of two Naked arrangements, two loop-less C-lobe (LCL) structures, and two FliC-based constructs. An LCL-based multi-epitope vaccine showed the best molecular docking score with human TLRs (TLR 1, 2, 4, and 5) and immune simulation results (Th1 cell population, IFN-γ, IL-12, IgM, IgG1, and IgG2 levels). This study provided a valuable library of exposed epitopes including 26 conserved, linear and immunogenic B-cell epitopes (belonged to 14 OMPs), and three optimized multi-epitope vaccines. However, more experimental studies are needed to confirm the actual immunoreactivity of these vaccine candidates. Highlights: Acinetobacter baumannii strains possess numerous highly immunogenic outer membrane proteins. LCL-6 and FliC-1 of A. baumannii as multi-epitope vaccines showed strong interactions with the TLRs. LCL-6 showed the best induction with acceptable levels of Th1 cell population, IgM, IgG1, IgG2, IFN-γ, and IL-12 levels.